Coconut: national and international scenario - Chowdappa, P; Jayasekhar, S (Indian Horticulture, 2018)
Among plantation crops, coconut is the major crop grown both under plantation and homestead management system. It provides livelihood security to several millions of people across the world, and capacity of coconut in providing improved nutrition, employment and income generation is well known. India produced 23,351 million nuts in the year 2011-12 from an area of 2.07 million ha with a productivity of 11,277 nuts/ha. The coconut palm exerts a profound influence on rural economy in many states where it is grown extensively and provides sustenance to more than 10 million people. The processing and related activities centered on the crop generate employment opportunities for over three million people in India. In addition, it contributes â‚¹ 92,000 million annually to the Gross Domestic Product (GDP) of the country. The coconut sector also contributes to foreign exchange earnings to the tune of â‚¹ 21,385 million through the export of coconut and coir products. Over 90% of coconut farmers in India are small holders and are considered resource-poor.